Survival Impact of Nephroureterectomy for De Novo Stage IV Nonmetastatic and Metastatic Upper Tract Urothelial Carcinoma - Lin, Wei-Yu; Lin, Meng-Hung; Yang, Yao-Hsu; Chen, Wen-Cheng; Huang, Cih-En; Chen, Miao-Fen; Wu, Chun-Te (Frontiers in Surgery, 2022)
Background Whether nephroureterectomy (NU) provides survival benefits in patients with stage IV upper tract urothelial carcinoma (UTUC) remains unclear. We compared the effect of chemotherapy (CT) alone with that of CT combined with NU (CT + NU) on the overall survival (OS) of patients with stage IV nonmetastatic UTUC (nmUTUC) and metastatic UTUC (mUTUC). Patients and Methods This multicenter retrospective cohort study included the data of patients with UTUC undergoing CT alone or CT + NU from the Chang Gung Cancer Database (2002–2015) and followed them until August 2017. OS and hazard ratios (HRs) were assessed using the Kaplan–Meier method and Cox proportional hazards model, respectively. Results This study included 308 patients with stage IV UTUC, comprising 139 with nmUTUC and 169 with mUTUC. Moreover, 91 (74.6%) patients with nmUTUC and 31 (25.4%) patients with mUTUC received NU. The CT + NU group had a higher 3-year OS rate (41.0.% vs 16.7%, p < 0.001), longer median OS duration (20.7 vs 9.0 months, p < 0.001), and lower risk of death (HR, 0.48; 95% confidence interval, 0.36–0.66; p < 0.001) than did the CT-alone group. Similarly, patients with mUTUC who underwent CT + NU had a longer median OS duration (25.0 vs 7.8 months, p < 0.001) and lower risk of death (HR, 0.37; 95% confidence interval, 0.23–0.59; p < 0.001) than did those who received CT alone. Conclusion Compared with CT alone, NU + CT can provide survival benefits to patients with nonmetastatic and metastatic stage IV UTUC.